Determinant factors influencing the reuse practice of heritage shop houses in the World Heritage City Melaka Core Zone / Nor Syahila Ab Rashid and Tim Heath - Ab Rashid, Nor Syahila; Heath, Tim (Faculty of Art and Design, 2024)
Rapid economic development and restructuring have an impact on the existence of more old buildings in large cities. Most of these buildings represent different eras and typologies. Like a shophouse in Southeast Asia that has its uniqueness, is a very important heritage. The desire to carry out research related to the reuse of shophouses arises from the condition of some of the city's assets that are abandoned and dilapidated. However, the maintenance of the shophouse with the original function may not be appropriate as the nature of use may change over time according to needs. Therefore, the practice of re-use is suggested to ensure that the building in question continues to be preserved and also to prevent obsolescence from being used as a justification for demolition. The objective of this research is to identify the most popular reuse options and the determining factors that influence the reuse of heritage shophouses in the Melaka Core Zone of the World Heritage City. This research uses survey (quantitative) and observation (qualitative) methods to gather information. Microsoft Excel and NVivo software were used to assist in the analysis of the collected data. Research findings show that cafes and restaurants are the most popular options for partial storefront repurposing, while hotels and motels are the most popular options for full storefront repurposing in this area. Legal provisions, tourism demand, inscription demand, profit, obsolete original function, building vacancy, and accessibility are identified as determining factors in the reuse practice. A deep understanding of the reuse process has the potential to be the basis of better policy formation to ensure that shops in this area remain actively functioning. The preservation of this building is important to maintain Melaka's recognition in the UNESCO World Heritage Site list on an ongoing basis.